The Effect of Online Learning on Interest in Studying Chemistry Courses - Norma Eralita; Siti Khuzaimah (International Journal of Chemistry Education Research, 2022)
The Covid-19 virus in 2020 had a tremendous impact on almost all fields, one of which was in the field of education. Online learning is a solution for teaching and learning activities during the Covid-19 pandemic. This study aims to determine the effect of online learning on interest in learning in chemistry courses during the Covid-19 pandemic. Respondents taken were students of the Faculty of Industrial Technology, University of Nahdlatul Ulama Al Ghazali, Cilacap. The research design used linear regression analysis, with the data collection method in the form of a questionnaire. The results of the analysis for the normality test show a sig value of 0.200 more than 0.05 which means the data is normally distributed and the results of the linearity test show a sig value of 0.393 more than 0.05 which means that the correlation between online learning variables and interest in learning is linear. Based on the results of the linear regression test, the regression coefficient of 0.779 is positive, so it can be said that the direction of the influence of the variable x on y is positive. Based on the significance value: the table coefficients obtained a significance value of 0.001 <0.05, so it can be concluded that the online learning variable (x) has an effect on the learning interest variable (y). Based on the t-count value of 3.607> t-table 2.0484, it can be concluded that the online learning variable (x) affects the learning interest variable (y)